Using Augmented Reality to engage STEM students with an authentic curriculum - M. Hobbs; D. Holley (European Alliance for Innovation (EAI), 2016)
This paper reports on the introduction of a set of 'Augmented Reality' (AR) tasks, offering an innovative, real world and problem based set of activities for a group of first year University Gaming and Computer Science students. Our initial research identifies a gap in the perceptions of STEM students between the usefulness of discipline based modules and a compulsory 'Professional Development' module where more 'employability' based skills were delivered. It had a history of poor student engagement and attendance, and failed to provide a compelling narrative/links to the outside world. The AR tasks were designed to facilitate group-working and multi-channel communication, and to engage students through the use of a more creative technology. Framed as a rich case study, insights are captured through student blogs, video interviews and a questionnaire. Initial findings indicate higher levels of satisfaction and an appreciation of groupwork tasks, enhanced student engagement and a greater awareness of the value of transferable skills.